Persepsi Perempuan Terhadap Tayangan Iklan Kecap ABC untuk Mendukung Hari Kesetaraan Perempuan - Yefi Dyan Nofa Harumike; Anita Reta Kusumawijayanti; Tarisa Elvira Trisna (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This study aims to explore women's perceptions of the advertisement "Kecap ABC Supports Equality in the Kitchen on Women’s Equality Day." Using a descriptive qualitative approach, the study involved 71 female students from the Communication Science Program, Faculty of Social and Political Sciences, Balitar Islamic University. Data were collected through an online questionnaire designed to analyze three main components of perception: cognitive, affective, and conative, concerning the message conveyed in the advertisement. The findings reveal that the majority of respondents possess a solid understanding of gender equality, particularly regarding men’s roles in domestic tasks. Most respondents responded positively to the advertisement, reflecting their support for the values of equality promoted. However, discrepancies in perceptions were noted in certain aspects, such as the ideal distribution of domestic responsibilities and the practical implementation of gender equality in family settings. This highlights the need for enhanced education and awareness, particularly on the importance of applying gender equality in daily life. This study provides valuable insights into how media can serve as an effective tool to promote the values of gender equality in society.